VD_FINDINFO HC / 2014 / 700 vom 8. September 2014 - VD Tribunal cantonal (2014)
TRANSACTION JUDICIAIRE, RÉPARTITION DES FRAIS | 106 al. 2 CPC (CH), 109 CPC (CH), 241 al. 2 CPC (CH), 241 al. 3 CPC (CH), 65 al. 2 TFJC (2010), 67 al. 2 TFJC (2010)